2014
DOI: 10.1063/1.4867198
|View full text |Cite
|
Sign up to set email alerts
|

Nonpolar resistive switching in Cu/SiC/Au non-volatile resistive memory devices

Abstract: Articles you may be interested in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 27 publications
5
37
0
Order By: Relevance
“…This suggests a noticeable contribution of the Schottky barrier at the amorphous GST/ TiN interfaces to the overall resistance. Similar behavior has also been observed in other metal/semiconductor memory device [17]. The disappearance of the Schottky barrier upon annealing could be due to the annealing process which is believed to improve the Schottky contacts between metal and semiconductor contacts [18], or due to the band gap reduction from amorphous state to crystalline state [19].…”
Section: Contact Resistancesupporting
confidence: 76%
“…This suggests a noticeable contribution of the Schottky barrier at the amorphous GST/ TiN interfaces to the overall resistance. Similar behavior has also been observed in other metal/semiconductor memory device [17]. The disappearance of the Schottky barrier upon annealing could be due to the annealing process which is believed to improve the Schottky contacts between metal and semiconductor contacts [18], or due to the band gap reduction from amorphous state to crystalline state [19].…”
Section: Contact Resistancesupporting
confidence: 76%
“…The a-SiC based RMs also show promising performance under high radiation conditions [4]. Despite the promising results thus far, it was also observed that relatively high forming voltage (VFORM), typically 4 to 5 V, were needed to switch a pristine a-SiC based RM into LRS [21]. This is likely attributable to the low Cu drift rate in SiC which requires high electric field to form the Cu filament in the a-SiC matrix.…”
Section: Introductionmentioning
confidence: 79%
“…Amorphous SiC shows great potential as the electrolyte layer with excellent state stability and ultra-high ratio memory cells, although slow to switch [2,3]. This was previously attributed to a high diffusion barrier of SiC for Cu along with high thermal conductivity [4].…”
Section: Introductionmentioning
confidence: 99%